(untitled) - Bobrowski, Steven M. (New York, 2006)
Take full advantage of all the powerful features available in Oracle Database 10g Express Edition with help from this easy-to-follow Oracle Press guide. Hands-On Oracle Database 10g Express Edition for Linux shows you, step by step, how to set up, administer, tune, troubleshoot, and secure a robust database system. You will also learn to use PL/SQL and Oracle Application Express to build custom database applications. Get started today with the Oracle database that's free to develop, deploy, and distribute.
Keywords: Database management,Online databases,Quản lý dữ liệu,Cơ sở dữ liệu trực tuyến